2022
DOI: 10.1038/s41467-022-31763-w
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile ferroelectric domain wall memory integrated on silicon

Abstract: Ferroelectric domain wall memories have been proposed as a promising candidate for nonvolatile memories, given their intriguing advantages including low energy consumption and high-density integration. Perovskite oxides possess superior ferroelectric prosperities but perovskite-based domain wall memory integrated on silicon has rarely been reported due to the technical challenges in the sample preparation. Here, we demonstrate a domain wall memory prototype utilizing freestanding BaTiO3 membranes transferred o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…LiNbO 3 is a well-known uniaxial ferroelectric in a rhombohedral (trigonal) symmetry with the spontaneous polarization aligned along the threefold Z-axis. The polarization charge at the CDW region in typical ferroelectrics acts as a movable dopant, enabling the free carrier concentration to be changed on demand by more than 10 orders of magnitude. , The doping density (∝2 P ·sinθ, where P is the polarization) would increase with the wall inclined angle, opening the door to tune the DW conduction for the application in the multilevel logic devices . Theoretical calculations by Shur et al, using the Landau–Ginzburg–Devonshire theory, showed that the hole mobility within the T–T DWs was at least 1 order of magnitude lower than the electron along the H–H DWs and the highest wall conduction would occur when θ = 90° rather than θ = 15° in Figure …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LiNbO 3 is a well-known uniaxial ferroelectric in a rhombohedral (trigonal) symmetry with the spontaneous polarization aligned along the threefold Z-axis. The polarization charge at the CDW region in typical ferroelectrics acts as a movable dopant, enabling the free carrier concentration to be changed on demand by more than 10 orders of magnitude. , The doping density (∝2 P ·sinθ, where P is the polarization) would increase with the wall inclined angle, opening the door to tune the DW conduction for the application in the multilevel logic devices . Theoretical calculations by Shur et al, using the Landau–Ginzburg–Devonshire theory, showed that the hole mobility within the T–T DWs was at least 1 order of magnitude lower than the electron along the H–H DWs and the highest wall conduction would occur when θ = 90° rather than θ = 15° in Figure …”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the wall currents are still insufficient to drive high-power nanodevices and fast memory circuits Figure shows the statistics of a typical linear wall current density of 2 × 10 –4 – 57 μA/μm among Pb­(Zr,Ti)­O 3 , , BaTiO 3 , , BiFeO 3 , ,,,− ErMnO 3 , ,, and LiNbO 3 ,,, ferroelectric materials. The values are correlated with the inclined wall angle (0° ≤ ±θ < 90°) of two different domains, and the resulting DWs can be divided into neutral (θ = 0°; NDW) and charged DWs (θ ≠ 0°; CDWs).…”
Section: Introductionmentioning
confidence: 99%
“…Polarization in the ferroelectric thin film is sensitive to external stimuli such as electric field, heat, light illumination, and mechanical force . When an external electric field is applied to force the local polarization switch to another direction, the switched polarization can polarize against the surrounding unswitched region by forming a charged domain wall (CDW). Once the conductive CDW bridges the electrodes at both ends of the capacitor, a wall current with magnitude much higher than the leakage value will be introduced driven by the bias voltage, resulting in significantly reduced resistance of the device. , The modulation of resistance by creating and erasing domain walls presents a promising approach to developing a nonvolatile resistive-switching memory that combines the advantages of high data storage density, nondestructive readout, and fast operation speed. Meanwhile, there are two other types of resistive-switching behaviors in ferroelectric devices. One is the polarization-modulated electrical tunneling when the ferroelectric thin film acts as the tunneling barrier, , and the other is the interfacial Schottky barrier modification depending on polarization reversal, also known as the “ferroelectric diode”. , Despite the difference in the functional region, all of the three resistance-switching mechanisms mentioned above rely on the manipulation of the ferroelectric polarization.…”
Section: Introductionmentioning
confidence: 99%
“…4−7 Once the conductive CDW bridges the electrodes at both ends of the capacitor, a wall current with magnitude much higher than the leakage value will be introduced driven by the bias voltage, resulting in significantly reduced resistance of the device. 8,9 The modulation of resistance by creating and erasing domain walls presents a promising approach to developing a nonvolatile resistive-switching memory that combines the advantages of high data storage density, nondestructive readout, and fast operation speed. 10−13 Meanwhile, there are two other types of resistive-switching behaviors in ferroelectric devices.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The ability of domain walls to form nonvolatile conductive channels, which can be moved, erased and recreated via electrical stimuli, and their plasticity hold promise for a variety of applications from memories to neuromorphic circuits. Since the first report of electrical transport properties of domain walls in BiFeO 3 (BFO) films 5 an impressive progress has been made in exploring different materials with domain wall conduction, demonstrating their functionalities 6 – 10 and advancing their technological relevance 11 . A nonvolatile ferroelectric domain wall memory has been proposed based on the formation of domain walls bridging two planar electrodes on a BFO film with insulating bottom interface 12 .…”
Section: Introductionmentioning
confidence: 99%